Update Methods of the Global National Environmental Accounting Database (NEAD) - Pan, Jiamin; Zhang, Hao; Wang, Xueqi; Liu, Gengyuan (Journal of Environmental Accounting and Management, 2026)
In this paper, we updated the existing emergy analysis framework and calculation methods of The Global National Environmental Accounting Database (NEAD) based on the fast-developed raw global environmental database and the replacements of the nations and regions. Latest GIS grid coverages for renewable flows, the processes of updating raw data necessary for tabular synthesis, and filtrating energy conversion rates and unit emergy values for translating physical flows to emergy units have been updated and standardized. This calculation methods framework incorporates a standardized template within which primary flows are calculated and aggregated into the emergy summary flows and indices. It could be used to formalize data sources, detail line items, calculate energy conversion calculations, and assign Unit Emergy Values (UEVs) to flows and will strengthen the power and credibility of comparative national emergy analysis.